In vitro synergistic activity of fosfomycin in combination with meropenem, amikacin and colistin against OXA-48 and/or NDM-producing Klebsiella pneumoniae - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2020)
Objective: Carbapenemase-producing Klebsiella pneumoniae (CPKp) infections are increasing worldwide. We investigated the in vitro synergistic activity of fosfomycin (FOS) with meropenem (MRP), amikacin (AMK) and colistin (COL) against OXA-48 and/or New Delhi metallo-beta-lactamase (NDM)-producing Kp blood isolates. Materials and Methods: Seventeen CPKp blood isolates were studied. The broth microdilution method was used for COL, MRP and AMK susceptibilities, while agar dilution for FOS. Synergy was tested by agar dilution chequerboard technique and also was confirmed by a time-kill assay for FOS/MRP and FOS/COL using three representative isolates that were found to be synergistic. Results: FOS in combination with MRP was found to be the most synergistic (15/17 strains, 88%), while 29% and 41% with AMK and COL, respectively. Antagonism was only determined in 2 isolates with the COL/FOS. Conclusions: The MRP/FOS combination demonstrated synergistic activity against CRKp, especially against the two common enzyme-producing isolates in Turkey (OXA-48 and NDM).
Keywords: Antagonism; antibiotic resistance; fosfomycin; arbapenemase; In Vitro synergy; Klebsiella pneumoniae; ANTIMICROBIAL SUSCEPTIBILITY; ANTIBACTERIAL ACTIVITY; ESCHERICHIA-COLI; URINARY-TRACT; CARBAPENEMASE; INFECTIONS; ENTEROBACTERIACEAE; MORTALITY; PHARMACOKINETICS; TIGECYCLINE